Quand l’écriture entre dans le quotidien : les mots de la mémoire dans les livres de raison (Provence, fin xve-xviiie siècles) - Isabelle Luciani (Lexis: Journal in English Lexicology)
Between the end of the Middle Ages and the beginning of the 19th century, handwriting, until then the bastion of a small number of literati, gradually became part of everyday family life. The “civilization of writing” was established, and it went along with the popularization (relative, as literacy rates slowly rose) of domestic writing. In the modern period, these included practical writings, of which the “livre de raison” (etymologically “account – ratio – book”) is one of the most interesting media, as it serves to express both the individual and the collective. These registers are beginning to be well known as objects of cultural and social history. And yet, as memorial artifacts whose dissemination was then historically unprecedented, they also constitute a novel corpus for Memory Studies, at the interdisciplinary crossroads of the human and cognitive sciences. Writing is in fact a way of fixing time, bringing into play procedural resources (recording, ordering, recalling, etc.), episodic and autobiographical resources, semantic resources (the past takes on meaning) and metacognitive resources. The contribution of “livres de raison” to the diachronic study of memory devices therefore deserves to be exploited today. Using a corpus of some 200 livres de raison drawn from Provençal archives of the 15th-18th centuries (municipal and departmental archives, public and private libraries), I propose to analyze the way in which a lexical semantics of memory is historically constructed in the crucible of ordinary language. These daily writings make up a heterogeneous corpus in terms of content and authors. From a magistrate in Parliament to a woman from the lower nobility using a clumsy, phonetic script, these scriptwriters fed their knowledge of memory from a variety of sources (school learning, self-taught, bookish cultures, oral cultures...) mobilized in different registers (domestic accounting, mercantile practices, family memories, professions of faith, personal diaries...) that intersected with a common point: the daily need to remember, and the new possibility of recording by themselves, and without depending on cultural intermediaries, what they wanted to remember, in what words and with what graphic devices. Working on the heterogeneous corpus of livres de raison in relation to literary corpora enable us to better understand the cultural registers and social interactions with which ordinary language integrated, appropriated or renewed the semantic field of memory in the practice of writing. This corpus, already transcribed in full in Word format, will then enable us to apprehend the common lexicon of memory (avoir bonne mémoire, se ressouvenir, enregistrer, marquer affin de cognoistre par le temps, tesmoigner etc.), particularly in the titles attributed to these registers by the scribes (Livre de Memoyres, cervant de memoire, Memoires mes affaires, Memoires du tempts, Memorial, Record et memoyre etc.), while the editorial and literary genre of the Mémoires was simultaneously being constructed. This lexicon is correlated with the functions of memory aids and records (these books of reason could be used as evidence in court), which allows us to question the way words and signs functioned in memory techniques (repetitions, reformulations, mnemonic use of genealogies, reference to historical events, etc.) developed by scribblers often unfamiliar with the learned “arts of memory”. The importance of the lexical field of the receptacle, combined with the regular use of deictics (en ce livre, en ce présent livre, dans lequel est conteneu tout ce que j’ay fait, C’est le livre de reison cervant de mémoire etc.) testifies to a concrete representation of memory as the site of a sedimentation of information for which the domestic book, a new memory artifact, guarantees “eternity”. This desire for permanence will lead us to question the memorial choices made by the writers, the product of a claimed selection (worthy of memory, worthy of note, the most important...), and the way in which some of them moved away from filling in of basic lists or rubrics, basic devices of the livre de raison, to develop a more narrative form, thus triggering a more or less fragmentary and assumed autobiographical gesture. By narrowing the focus, we will be looking at the subject’s reflexivity in the face of the memory process: what he or she knows about it, how he or she represents it, how he or she situates himself or herself in a collective memory, and whether, more rarely, he or she allows himself or herself to preserve personal memories. For such writers, putting memory into words aims to preserve but also reactivate memories. Their practice can thus develop a "literary" aspect within ordinary writing, raising the question of the historicity of narrative modes and the role of emotions (nostalgia, for example) in memory processes.